(untitled) (World Bulletin of Social Sciences, 2026)
This article examines the concept of autism, its causes, and its main symptoms. It defines autism and explains its essence. It also describes the conditions under which autism manifests itself and its treatment methods. The article examines the main symptoms and causes of autism in detail, summarizes the findings, and presents suggestions and recommendations for treatment methods.